Clinical Observation and Prognostic Analysis of Patients With Klebsiella pneumoniae Bloodstream Infection - Zhang, Shuguang; Yang, Ziyue; Sun, Limin; Wang, Zhenhua; Sun, Liutao; Xu, Jinli; Zeng, Li; Sun, Tongwen (Frontiers in Cellular and Infection Microbiology, 2020)
Background and Purpose: The clinical prognosis of Klebsiella pneumoniae bloodstream infection is poor, and the prevalence of drug-resistant bacteria makes clinical anti-infective treatment more challenging. This retrospective study evaluated the epidemiological characteristics of patients with Klebsiella pneumoniae, the risk factors for drug-resistant bacterial infection and death, and analyzed treatment options. Methods: Clinical data of 297 patients diagnosed with Klebsiella pneumoniae bacteremia between June 2014 and June 2019 were collected. Results: Intensive care unit hospitalization history, operation history, recent antibiotic use history, mechanical ventilation, and number of days hospitalized before bloodstream infection were found to be independent risk factors for drug-resistant bacterial infection. The risk of death for carbapenem-resistant Klebsiella pneumoniae infection was 2.942 times higher than that for carbapenem-sensitive Klebsiella pneumoniae infection. For extensively drug-resistant Klebsiella pneumoniae bacteremia patients, the mortality rate of combined anti-infective therapy was lower. Conclusions: Clinicians should pay attention to patients with high-risk drug-resistant bacteria infection and administer timely anti-infection treatment. The findings of this study may provide some suggestions for early identification and standardized treatment of patients with Klebsiella pneumoniae bacteremia.